2019
DOI: 10.1177/2333392818822914
|View full text |Cite
|
Sign up to set email alerts
|

Rural Primary Care Offices and Cancer Survivorship Care: Part of the Care Trajectory for Cancer Survivors

Abstract: Background:A cancer diagnosis is a monumental event in a patient’s life and with the number of cancer survivors increasing; most of these patients will be taken care of by a primary care provider at some point after their cancer therapy. The purpose of this study is to identify primary care physician’s needs to care for a patient who has had cancer.Methods:A cross-sectional survey of the physician members of the Iowa Research Network was conducted. The survey was designed to measure physician confidence in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Even though PCPs generally reported good or adequate skills in detecting recurrences [21-23, 34, 49] and providing follow-up care [21,22,35,49], their confidence to do so was rated much lower than their knowledge [21,29,31,32,34,49]. While our study did not address these factors, others have found lower confidence levels related to fewer (years of) experience [26, 31-34, 38, 39] and female sex [26,30,33,39]. Confidence may also be related to the cancer survivor population of interest [29,45,51] as PCPs may only see a limited number of patients with particular types of cancer.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Even though PCPs generally reported good or adequate skills in detecting recurrences [21-23, 34, 49] and providing follow-up care [21,22,35,49], their confidence to do so was rated much lower than their knowledge [21,29,31,32,34,49]. While our study did not address these factors, others have found lower confidence levels related to fewer (years of) experience [26, 31-34, 38, 39] and female sex [26,30,33,39]. Confidence may also be related to the cancer survivor population of interest [29,45,51] as PCPs may only see a limited number of patients with particular types of cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Knowledge and confidence in management of physical effects was described in 13 studies. About half of these studies (n = 7) did not specify the physical effect under evaluation [21,22,24,32,39,49,51], while others (n = 6) focused on specific symptoms, such as fatigue and treatment-related osteoporosis [26,28,[36][37][38]40]. Only four studies examined knowledge of PCPs regarding physical effects [24,28,36,40].…”
Section: Surveillance and Management Of Physical Effectsmentioning
confidence: 99%
See 3 more Smart Citations